Validitas Buku Ajar dengan Pendekatan Kontekstual berbasis Budaya untuk Membelajarkan kreativitas Menulis Karangan Siswa - Reviva Safitri; Zefri Faizal; Sabri Sabri (Jurnal Ilmiah Global Education, 2026)
Junior high school students' writing creativity is often limited by the materials and approaches used in teaching materials. Contextual materials integrated with local wisdom can provide meaningful learning experiences. This study used a research and development model (preliminary research, prototyping, assessment) to design a contextual-based textbook containing local cultural values. The study participants included 34 students in the experimental class, 32 students in the control class, and 3 expert validators. Data were collected through validation, observation, questionnaires, and a pretest-posttest creativity test. The textbook achieved high validity (90.63%), with implementation in the classroom rated very good (mean score 4.77). Writing creativity increased significantly in the experimental group compared to the control group (t = 7.049; p < 0.05), with a higher N-Gain (0.64 vs. 0.36). Practicality scores from students (84.51%) and teachers were also high. Conclusion: Contextual-based textbooks that integrate local cultural wisdom are valid, practical, and effective in improving students' creativity in writing narrative essays.